PENINGKATAN NILAI EKONOMI BUAH PISANG MELALUI PENGOLAHAN PIE PISANG KHAS LAMPUNG - Muhammad Saputra; Novita Sari (Dedication : Jurnal Pengabdian Masyarakat, 2018)
Community service activities are conducted with the aim to improve the skills of Woman Islamic Religius Club processing banana fruit into a product that has a higher economic value into a banana pie. Merbau Mataram District is one of 17 districts in Lampung Selatan District, Lampung Province. Merbau Mataram Sub-district of South Lampung Regency has great potential to be developed, among others, in the plantation sector in the form of bananas. The harvest of bananas is mostly only consumed by themselves because of the economical selling point in the sub-district market that is not so profitable. In Baru Ranji Village there is a Woman Ismic Religius Club . On a regular basis they meet in a mosque or in one of the residents' houses to conduct a study of al-qur'an together and listen to lectures delivered by the ustadzah who are invited to Fill out the review. After the recitation of the study, it is only filled with activities that have no economic benefits. Based on the problem there is an opportunity for devotees to perform activities of service to the community with the object of Woman Islamic Religius Club. They can be taught skills to use bananas to be processed into banana pie.